GAGALNYA PERLINDUNGAN ANAK SEBAGAI SALAH SATU BAGIAN DARI HAK ASASI MANUSIA OLEH ORANG TUA DITINJAU DARI MAZHAB UTILITARIANISME - Simbolon, Laurensius Arliman (Jurnal Yuridis, 2016)
Protection of children's rights are elements of the Human Rights. Efforts to protect the rights and future of the children were violated by the state, the adults, the environment itself, and parents are still not so noticed. Though children are soulmates, picture and mirror the future, asset family, religion and nation. Child Protection Act has given sanction to any parents who fail to provide protection to children. Cases against parents who fail to protect the rights of his son, then according to the authors it has violated the children's rights are part of human rights. There are two forms of compliance required by children, namely in terms of the act and the other terms of the rules that are responsive and nature gives happiness. Continuing to child protection, it requires continuous legal justice for children, ongoing legal certainty for the child and the benefit of ongoing legal for children.